Preparation method of self-supporting electrolyzed water anode containing trace precious metal acid-resistant oxygen evolution catalyst

By embedding a small amount of precious metals in the non-precious metal matrix, an acid-resistant oxygen evolution catalyst is prepared and applied to carbon-based paper to form a self-supported electrolytic anode, which solves the problem of low oxygen evolution reaction efficiency in electrolytic water hydrogen production, and achieves efficient, stable and economical catalytic effects.

CN119593004APending Publication Date: 2025-03-11ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411869173.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, oxygen evolution reaction (OER) has become a key bottleneck restricting overall efficiency due to its high overpotential and slow reaction kinetics. Especially under extremely acidic conditions, the high cost and scarcity of traditional precious metal catalysts limit their wide application.

Method used

By embedding a very small amount of precious metals, such as platinum or iridium, into a non-precious metal matrix, a unique heterostructure is formed. Combined with ball milling and ultrasonic treatment technology, an acid-resistant oxygen evolution catalyst containing trace amounts of precious metals is prepared and applied to carbon-based paper to form a self-supported electrolytic water anode.

Benefits of technology

It realizes efficient oxygen evolution reaction in an acidic environment, significantly reduces the use of precious metals, improves the stability and life of the catalyst, reduces production costs, and improves the economic benefits of hydrogen production by electrolyzing water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593004A_ABST
    Figure CN119593004A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a self-supporting electrolyzed water anode containing a trace precious metal acid-resistant oxygen evolution catalyst, and belongs to the technical field of electro-catalysis electrode preparation and electrochemistry. The method comprises the following steps: firstly, preparing a nitrate aqueous solution and a noble metal chlorination solution, mixing the nitrate aqueous solution and the noble metal chlorination solution according to the atomic molar ratio of noble metal to non-noble metal of 1: 100, adding the mixed solution into a PE (Poly Ethylene) ball milling tank for ball milling, mixing the ball-milled solution with ethanol, and performing ultrasonic treatment to obtain a catalytic solution; and smearing the catalytic solution on the carrier, drying under an infrared lamp, and finally annealing in a muffle furnace. According to the method, the economic benefit of hydrogen production by electrolysis of water can be remarkably improved, the commercialization process of a renewable energy source technology can be promoted, the limitation of a traditional OER catalyst is broken through through fine regulation and control on material components, structures and preparation conditions, a better solution is provided for oxygen evolution reaction in an acid environment, and the method is suitable for industrial production. And a green, low-carbon and sustainable energy system is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrocatalytic electrode preparation and electrochemical technology, and specifically is a method for preparing a self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst. Background Art

[0002] At present, the demand for clean energy is increasing day by day around the world. Especially in the context of addressing climate change and reducing greenhouse gas emissions, it is particularly important and urgent to find efficient, economical and sustainable energy conversion technologies. With the guidance of the "dual carbon" goals, the support of national policies, the increasing maturity of technology and the sharp decline in costs, hydrogen energy is ushering in a strategic opportunity period for rapid development. Expanding hydrogen production capacity and increasing the proportion of green hydrogen are the future trends of global energy development. At present, my country's hydrogen production industry still uses fossil energy as the main raw material, and the proportion of clean hydrogen production has lagged behind some countries, so vigorously developing green hydrogen has important strategic significance and practical application significance.

[0003] Hydrogen production by water electrolysis is a promising green energy solution that can convert excess renewable energy into hydrogen fuel that is easy to store and transport, and is expected to become a key bridge connecting renewable electricity and terminal energy consumption. However, in the process of water electrolysis, the oxygen evolution reaction (OER) becomes a key bottleneck restricting the overall efficiency due to its high overpotential and slow reaction kinetics. For this reason, the development of efficient and stable OER catalysts, especially catalysts that can work in a strong acidic environment, has become a hot topic in current research.

[0004] Traditionally, noble metals such as iridium (Ir) and ruthenium (Ru) are considered the most effective catalysts for OER, but their widespread application has been greatly hindered by the dual limitations of high cost and scarcity. In recent years, scientists have been committed to exploring low-cost alternatives, including non-noble metal catalysts based on abundant metals such as iron (Fe), cobalt (Co), and nickel (Ni). Although these materials show certain catalytic activity, they often face problems such as insufficient activity and poor stability, especially under extremely acidic conditions. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a self-supporting anode for water electrolysis containing a trace amount of noble metal acid-resistant oxygen evolution catalyst, aiming to combine the high catalytic activity of noble metals with the low cost and stability of transition metals to achieve the preparation of a new type of OER catalyst self-supporting anode for water electrolysis with high efficiency, corrosion resistance and long life. Through the method of the present invention, a working electrode with excellent performance and stability can be obtained by adding a very small amount of noble metals.

[0006] The present invention is achieved through the following technical solutions: A method for preparing a self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst comprises the following steps: 1) Dissolve various nitrates in deionized water to prepare various 2.0 M nitrate aqueous solutions as precursors; at the same time, prepare 20 mg / ml noble metal chloride solutions.

[0007] 2) First, the various nitrate aqueous solutions prepared in step 1) are mixed in an equal molar ratio of non-precious metals, and then the precious metal chloride solution prepared in step 1) is added, and the amount of the precious metal chloride solution added is added in a ratio of 1:100 of precious metal to non-precious metal molar ratio, and finally a mixed solution is obtained.

[0008] 3) Select the mixed solution prepared in step 2) and add it into a PE ball mill for sufficient ball milling and oscillation.

[0009] 4) The mixed solution after sufficient oscillation in step 3) is mixed with ethanol and subjected to ultrasonic treatment to improve the wettability of the mixed solution to obtain a catalytic solution.

[0010] 5) Apply the catalytic solution prepared in step 4) on the carrier, apply the catalytic solution on both the front and back sides of the carrier, and dry it under an infrared lamp to ensure that the dripped catalytic solution is dry and does not flow.

[0011] 6) placing the carrier loaded and dried in step 5) in a muffle furnace, heating it to 400° C. and annealing it in air, then rinsing the annealed carrier with deionized water and drying it, and finally obtaining the self-supporting water electrolysis anode containing a trace amount of precious metal acid-resistant oxygen evolution catalyst.

[0012] Furthermore, in step 1), the plurality of 2.0 M nitrate aqueous solutions prepared are two or three of Fe(NO3)3·9H2O, Co(NO3)2·6H2O, and Ni(NO3)2·6H2O.

[0013] Furthermore, in step 1), the prepared noble metal chloride solution is a platinum tetrachloride aqueous solution or an iridium trichloride aqueous solution.

[0014] Furthermore, in step 3), 1.5 ml of the mixed solution was added to a PE ball mill, and then zirconium oxide microspheres were added. The speed was set to 5000 rpm and the time was 180 s. The mixture was fully shaken 10 times every half an hour.

[0015] Furthermore, in step 4), the mixed solution after sufficient oscillation is mixed with ethanol in an equal volume ratio of 1:1, the ultrasonic treatment time is 30 minutes, and the concentration of ethanol is 99.7%.

[0016] Furthermore, in step 5), the carrier is raw carbon paper TGPH060.

[0017] Furthermore, in step 5), the cutting size of the raw carbon paper TGPH060 is 1*2 cm, the amount of the catalytic solution applied on the front and back sides is 40 μl, the application area is 1*1 cm, and the drying time under the infrared lamp is 10 min.

[0018] Furthermore, in step 6), after the carrier is placed in the muffle furnace, the temperature of the muffle furnace is increased to 400° C. at a rate of 5° C. / min, maintained for 1 hour, and then cooled naturally.

[0019] The self-supporting water electrolysis anode containing trace amounts of noble metal acid-resistant oxygen evolution catalysts described in the present invention can not only significantly improve the economic benefits of water electrolysis to produce hydrogen, but also promote the commercialization of renewable energy technologies, making important contributions to accelerating global energy transformation. Through the fine control of material composition, structure and preparation conditions, the limitations of traditional OER catalysts are broken, providing a better solution for oxygen evolution reaction in acidic environments, thereby helping to achieve a green, low-carbon, and sustainable energy system.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1) The present invention adopts the principle of complementary metal properties and embeds a small amount of precious metals (such as platinum, iridium, etc.) into non-precious metal matrices such as iron, cobalt, and nickel to form a unique heterostructure; the presence of precious metal particles not only increases the number of catalytic active centers, but also promotes the efficiency of electron transfer and enhances the overall catalytic performance of the material.

[0021] 2) The surface of the specially designed composite material of the present invention is specially treated to form a strong protective layer, which can maintain stability even under extremely acidic conditions, accurately control the size and distribution of the precious metal particles, ensure that each precious metal particle can play the maximum role, prevent the loss of precious metals, avoid waste, and extend the service life of the catalyst.

[0022] 3) The catalyst self-supporting water electrolysis anode prepared by the present invention exhibits excellent OER activity in acidic electrolyte, has low overpotential, and can remain stable under long-term operation, showing high catalytic efficiency and durability, providing a more reliable solution for hydrogen production by water electrolysis, which is significantly better than most similar products currently on the market.

[0023] 4) The method of the present invention significantly saves the waste of precious metals while maintaining or even exceeding the original catalytic efficiency. The present invention uses non-precious metals as catalyst components, avoids excessive reliance on precious metals that are scarce and have large price fluctuations, and reduces production costs. At the same time, the preparation process of the present invention is simple, the raw materials are easily available, no complicated equipment is required, the products are stable and reliable, and it has good potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic diagram of a self-supporting water electrolysis anode containing a trace amount of precious metal acid-resistant oxygen evolution catalyst prepared in Example 1 of the present invention.

[0025] Figure 2 This is a graph showing the test results of the electrolysis stability of the self-supporting water electrolysis anode containing trace amounts of precious metal acid-resistant oxygen evolution catalyst prepared in Example 1 of the present invention in a 0.5M H2SO4 solution.

[0026] Figure 3 The self-supporting water electrolysis anode containing trace precious metal acid-resistant oxygen evolution catalyst prepared in Example 1 of the present invention is 10 mA / cm 2 Schematic diagram of stable operation under current density.

[0027] Figure 4 This is a graph showing the test results of the electrolysis stability of the self-supporting water electrolysis anode containing trace amounts of precious metal acid-resistant oxygen evolution catalyst prepared in Example 2 of the present invention in a 0.5M H2SO4 solution. DETAILED DESCRIPTION

[0028] In order to more clearly illustrate the preparation method of the self-supporting water electrolysis anode containing trace precious metal acid-resistant oxygen evolution catalyst and its product performance, the following is further described by specific examples. It should be particularly noted that the specific examples described herein are only used to explain the present invention and are not intended to limit the present invention. Example 1

[0029] A method for preparing a self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst comprises the following steps: 1) Dissolve Co(NO3)2 and Ni(NO3)2 in deionized water to prepare 2.0M Co(NO3)2·6H2O aqueous solution and 2.0M Ni(NO3)2·6H2O aqueous solution as precursors; at the same time, prepare 20mg / ml PtCl4 aqueous solution.

[0030] 2) First, the Co(NO3)2·6H2O aqueous solution and the Ni(NO3)2·6H2O aqueous solution prepared in step 1) are mixed in an equimolar ratio of Co to Ni, and then the PtCl4 aqueous solution prepared in step 1) is added, and the amount of the PtCl4 aqueous solution added is added in a ratio of Pt to Co of 1:100, and finally a mixed solution of Co(NO3)2·6H2O, Ni(NO3)2·6H2O and PtCl4 is obtained.

[0031] 3) Select 1.5 ml of the mixed solution of Co(NO3)2·6H2O, Ni(NO3)2·6H2O and PtCl4 prepared in step 2) and add it to a PE ball mill, then add zirconium oxide microspheres, set the speed to 5000 rpm and the time to 180 s, and oscillate thoroughly 10 times every half an hour; to ensure complete oscillation and sufficient ball milling, the PE ball mill used is a micro high-speed vibration ball mill, model MSK-SFM-12M-220V.

[0032] 4) The mixed solution of Co(NO3)2·6H2O, Ni(NO3)2·6H2O and PtCl4 after sufficient shaking in step 3) was mixed with 99.7% ethanol in an equal volume of 1:1 and subjected to ultrasonic treatment for 30 minutes to improve the wettability of the mixed solution to obtain a catalytic solution.

[0033] 5) Apply the catalytic solution prepared in step 4) on the raw carbon paper TGPH060 cut to a size of 1*2 cm. The catalytic solution is applied to both sides of the raw carbon paper TGPH060. The amount of catalytic solution applied on each side is 40 μl and the application area is 1*1 cm. Apply continuously to ensure that the applied catalytic solution is evenly distributed. Finally, dry it under an infrared lamp for 10 minutes to ensure that the dripped catalytic solution is dry and does not flow.

[0034] 6) The raw carbon paper TGPH060 loaded and dried in step 5) is placed in a muffle furnace, and the temperature of the muffle furnace is raised to 400°C at a rate of 5°C / min. After maintaining for 1 hour, the temperature is naturally cooled and annealed in air. The annealed carrier is then rinsed with deionized water and dried to finally obtain a self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst, such as Figure 1 shown.

[0035] The electrochemical performance test of the self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst prepared in Example 1 is as follows: In 25 o C, in a 0.5 M H2SO4 solution, a three-electrode system was used with a graphite rod as a counter electrode, Hg / Hg2SO4 as a reference electrode, and the self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst prepared in Example 1 as a working electrode, and a CHI660e electrochemical workstation was used to test the catalytic performance of the working electrode.

[0036] Figure 2The figure is a test result of the electrolysis stability of the self-supporting anode for water electrolysis containing trace amounts of noble metal acid-resistant oxygen evolution catalyst in 0.5M H2SO4 solution prepared in Example 1. The analysis of the figure shows that the change in oxygen evolution potential is extremely small, which proves the extremely strong stability of the self-supporting anode for water electrolysis containing trace amounts of noble metal acid-resistant oxygen evolution catalyst prepared in Example 1.

[0037] Figure 3 The self-supporting water electrolysis anode containing trace precious metal acid-resistant oxygen evolution catalyst prepared in Example 1 was 10 mA / cm 2 Schematic diagram of stable operation under current density. It can be seen from the figure that its operation is very stable. Example 2

[0038] A method for preparing a self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst comprises the following steps: 1) Dissolve Co(NO3)2 and Fe(NO3)3 in deionized water to prepare 2.0M Co(NO3)2·6H2O aqueous solution and 2.0M Fe(NO3)3·9H2O aqueous solution as precursors; at the same time, prepare 20mg / ml PtCl4 aqueous solution.

[0039] 2) First, the Co(NO3)2·6H2O aqueous solution and the Fe(NO3)3·9H2O aqueous solution prepared in step 1) are mixed in an equimolar ratio of Co to Fe, and then the PtCl4 aqueous solution prepared in step 1) is added, and the amount of the PtCl4 aqueous solution added is added in a ratio of Pt to Co of 1:100, and finally a mixed solution of Co(NO3)2·6H2O, Fe(NO3)3·9H2O and PtCl4 is obtained.

[0040] 3) Select 1.5 ml of the mixed solution of Co(NO3)2·6H2O, Fe(NO3)3·9H2O and PtCl4 prepared in step 2) and add it to a PE ball mill, then add zirconium oxide microspheres, set the speed to 5000 rpm and the time to 180 s, and oscillate thoroughly 10 times every half an hour; to ensure complete oscillation and sufficient ball milling, the PE ball mill used is a micro high-speed vibration ball mill, model MSK-SFM-12M-220V.

[0041] 4) The mixed solution of Co(NO3)2·6H2O, Fe(NO3)3·9H2O and PtCl4 after sufficient shaking in step 3) was mixed with 99.7% ethanol in an equal volume ratio of 1:1 and subjected to ultrasonic treatment for 30 minutes to improve the wettability of the mixed solution to obtain a catalytic solution.

[0042] 5) Apply the catalytic solution prepared in step 4) on the raw carbon paper TGPH060 cut to a size of 1*2 cm. The catalytic solution is applied to both sides of the raw carbon paper TGPH060. The amount of catalytic solution applied on each side is 40 μl and the application area is 1*1 cm. Apply continuously to ensure that the applied catalytic solution is evenly distributed. Finally, dry it under an infrared lamp for 10 minutes to ensure that the dripped catalytic solution is dry and does not flow.

[0043] 6) The raw carbon paper TGPH060 loaded and dried in step 5) is placed in a muffle furnace, and the temperature of the muffle furnace is raised to 400°C at a rate of 5°C / min. After maintaining for 1 hour, it is naturally cooled and annealed in air. The annealed carrier is then rinsed with deionized water and dried to finally obtain a self-supporting water electrolysis anode containing a trace amount of precious metal acid-resistant oxygen evolution catalyst.

[0044] The electrochemical performance of the self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst prepared in Example 2 was tested as follows: In 25 o C, in 0.5 M H2SO4 solution, a three-electrode system was used with a graphite rod as the counter electrode, Hg / Hg2SO4 as the reference electrode, and the self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst prepared in Example 2 as the working electrode, and the catalytic performance of the working electrode was tested using a CHI660e electrochemical workstation.

[0045] Figure 4 This is a graph showing the electrolysis stability test results of the self-supporting anode for water electrolysis containing trace amounts of noble metal acid-resistant oxygen evolution catalysts in 0.5M H2SO4 solution prepared in Example 2. The graph shows that the change in oxygen evolution potential is extremely small, proving the extremely strong stability of the self-supporting anode for water electrolysis containing trace amounts of noble metal acid-resistant oxygen evolution catalysts prepared in Example 2. Example 3

[0046] A method for preparing a self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst comprises the following steps: 1) Dissolve Ni(NO3)2 and Fe(NO3)3 in deionized water to prepare 2.0M Ni(NO3)2·6H2O aqueous solution and 2.0M Fe(NO3)3·9H2O aqueous solution as precursors; at the same time, prepare 20mg / ml PtCl4 aqueous solution.

[0047] 2) First, the Ni(NO3)2·6H2O aqueous solution and the Fe(NO3)3·9H2O aqueous solution prepared in step 1) are mixed in an equimolar ratio of Ni to Fe, and then the PtCl4 aqueous solution prepared in step 1) is added, and the amount of the PtCl4 aqueous solution added is added in a ratio of Pt to Ni of 1:100, and finally a mixed solution of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O and PtCl4 is obtained.

[0048] 3) Select 1.5 ml of the mixed solution of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O and PtCl4 prepared in step 2) and add it to a PE ball mill, then add zirconium oxide microspheres, set the speed to 5000 rpm and the time to 180 s, and perform thorough ball milling and oscillation 10 times every half an hour; to ensure complete and sufficient oscillation and ball milling, the PE ball mill used is a micro high-speed vibration ball mill, model MSK-SFM-12M-220V.

[0049] 4) The mixed solution of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O and PtCl4 after sufficient shaking in step 3) was mixed with 99.7% ethanol in a ratio of 1:1 and subjected to ultrasonic treatment for 30 minutes to improve the wettability of the mixed solution to obtain a catalytic solution.

[0050] 5) Apply the catalytic solution prepared in step 4) on the raw carbon paper TGPH060 cut to a size of 1*2 cm. The catalytic solution is applied to both sides of the raw carbon paper TGPH060. The amount of catalytic solution applied on each side is 40 μl and the application area is 1*1 cm. Apply continuously to ensure that the applied catalytic solution is evenly distributed. Finally, dry it under an infrared lamp for 10 minutes to ensure that the dripped catalytic solution is dry and does not flow.

[0051] 6) The raw carbon paper TGPH060 loaded and dried in step 5) is placed in a muffle furnace, and the temperature of the muffle furnace is raised to 400°C at a rate of 5°C / min. After maintaining for 1 hour, it is naturally cooled and annealed in air. The annealed carrier is then rinsed with deionized water and dried to finally obtain a self-supporting water electrolysis anode containing a trace amount of precious metal acid-resistant oxygen evolution catalyst. Example 4

[0052] A method for preparing a self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst comprises the following steps: 1) Dissolve Co(NO3)2, Ni(NO3)2 and Fe(NO3)3 in deionized water to prepare 2.0M Co(NO3)2·6H2O aqueous solution, 2.0M Ni(NO3)2·6H2O aqueous solution and 2.0M Fe(NO3)3·9H2O aqueous solution as precursors; at the same time, prepare 20mg / ml lrCl3 aqueous solution.

[0053] 2) First, the Co(NO3)2·6H2O aqueous solution, Ni(NO3)2·6H2O aqueous solution and Fe(NO3)3·9H2O aqueous solution prepared in step 1) are mixed in equal molar proportions of Co, Ni and Fe, and then the lrCl3 aqueous solution prepared in step 1) is added, and the amount of lrCl3 aqueous solution added is added in a ratio of lr to Co of 1:100, and finally a mixed solution of Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Fe(NO3)3·9H2O and lrCl3 is obtained.

[0054] 3) Select 1.5 ml of the mixed solution of Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Fe(NO3)3·9H2O and lrCl3 prepared in step 2) and add it to a PE ball mill, then add zirconium oxide microspheres, set the speed to 5000 rpm and the time to 180 s, and perform thorough ball milling and oscillation 10 times every half an hour; to ensure complete and sufficient oscillation and ball milling, the PE ball mill used is a micro high-speed vibration ball mill, model MSK-SFM-12M-220V.

[0055] 4) The mixed solution of Co(NO3)2·6H2O, Ni(NO3)2·6H2O, Fe(NO3)3·9H2O and lrCl3 after sufficient shaking in step 3) was mixed with 99.7% ethanol in a ratio of 1:1 and subjected to ultrasonic treatment for 30 minutes to improve the wettability of the mixed solution to obtain a catalytic solution.

[0056] 5) Apply the catalytic solution prepared in step 4) on the raw carbon paper TGPH060 cut to a size of 1*2 cm. The catalytic solution is applied to both sides of the raw carbon paper TGPH060. The amount of catalytic solution applied on each side is 40 μl and the application area is 1*1 cm. Apply continuously to ensure that the applied catalytic solution is evenly distributed. Finally, dry it under an infrared lamp for 10 minutes to ensure that the dripped catalytic solution is dry and does not flow.

[0057] 6) The raw carbon paper TGPH060 loaded and dried in step 5) is placed in a muffle furnace, and the temperature of the muffle furnace is raised to 400°C at a rate of 5°C / min. After maintaining for 1 hour, it is naturally cooled and annealed in air. The annealed carrier is then rinsed with deionized water and dried to finally obtain a self-supporting water electrolysis anode containing a trace amount of precious metal acid-resistant oxygen evolution catalyst.

[0058] The above description is only a preferred specific implementation manner of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention should be included in the scope of protection of the invention.

Claims

1. A method for preparing a self-supporting water electrolysis anode containing a trace amount of noble metal acid-resistant oxygen evolution catalyst, characterized in that: The following steps are involved: 1) Dissolve various nitrates in deionized water to prepare various 2.0M nitrate aqueous solutions as precursors; at the same time, prepare 20 mg / ml noble metal chloride solutions; 2) firstly, the various nitrate aqueous solutions prepared in step 1) are mixed in an equal molar ratio of non-precious metals, and then the noble metal chloride solution prepared in step 1) is added, wherein the noble metal chloride solution is added in an amount according to a molar ratio of noble metal to non-precious metal of 1:100, and finally a mixed solution is obtained; 3) Select the mixed solution prepared in step 2) and add it into a PE ball milling tank for sufficient ball milling and oscillation; 4) mixing the mixed solution after sufficient oscillation in step 3) with ethanol and performing ultrasonic treatment to improve the wettability of the mixed solution to obtain a catalytic solution; 5) Apply the catalytic solution prepared in step 4) on the carrier, apply the catalytic solution on both the front and back sides of the carrier, and dry it under an infrared lamp to ensure that the dripped catalytic solution is dry and does not flow; 6) placing the carrier loaded and dried in step 5) in a muffle furnace, heating it to 400° C. and annealing it in air, then rinsing the annealed carrier with deionized water and drying it, and finally obtaining the self-supporting water electrolysis anode containing a trace amount of precious metal acid-resistant oxygen evolution catalyst.

2. The method for preparing a self-supporting anode for water electrolysis containing a trace amount of noble metal acid-resistant oxygen evolution catalyst according to claim 1, characterized in that: In step 1), the multiple 2.0M nitrate aqueous solutions prepared are two or three of Fe(NO3)3·9H2O, Co(NO3)2·6H2O, and Ni(NO3)2·6H2O.

3. The method for preparing a self-supporting anode for water electrolysis containing a trace amount of noble metal acid-resistant oxygen evolution catalyst according to claim 1, characterized in that: In step 1), the prepared noble metal chlorination solution is a platinum tetrachloride aqueous solution or an iridium trichloride aqueous solution.

4. The method for preparing a self-supporting anode for water electrolysis containing a trace amount of noble metal acid-resistant oxygen evolution catalyst according to claim 1, characterized in that: In step 3), select 1.5 ml of the mixed solution and add it to the PE ball mill, then add zirconium oxide microspheres, set the speed to 5000 rpm and the time to 180 s, and shake it thoroughly 10 times every half an hour.

5. The method for preparing a self-supporting anode for water electrolysis containing a trace amount of noble metal acid-resistant oxygen evolution catalyst according to claim 1, characterized in that: In step 4), the mixed solution after sufficient shaking was mixed with ethanol in an equal volume ratio of 1:1, the ultrasonic treatment time was 30 minutes, and the concentration of ethanol was 99.7%.

6. The method for preparing a self-supporting anode for water electrolysis containing a trace amount of noble metal acid-resistant oxygen evolution catalyst according to claim 1, characterized in that: In step 5), the carrier is raw carbon paper TGPH060.

7. The method for preparing a self-supporting anode for water electrolysis containing a trace amount of noble metal acid-resistant oxygen evolution catalyst according to claim 6, characterized in that: The cutting size of the raw carbon paper TGPH060 is 1*2 cm, the amount of the catalytic solution applied on the front and back sides is 40 μl, the application area is 1*1 cm, and the drying time under the infrared lamp is 10 min.

8. The method for preparing a self-supporting anode for water electrolysis containing a trace amount of noble metal acid-resistant oxygen evolution catalyst according to claim 1, characterized in that: In step 6), after the carrier is placed in the muffle furnace, the temperature of the muffle furnace is raised to 400° C. at a rate of 5° C. / min, maintained for 1 hour, and then cooled naturally.